Identitas Profesional Guru Sekolah Dasar Berdasarkan Pengalaman Mengajar: Tinjauan Filosofis, Teoritis dan Praktis - Siti Resmi Sahara; Arie Rakhmat Riyadi; Neni Maulidah (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2025)
The professional identity of elementary school teachers is a dynamic construction formed through the interaction between knowledge, values, teaching experience, and self-reflection. This article aims to examine how the teaching experience of teachers, both novice and senior, contributes to the formation of their professional identity. This study uses a qualitative approach with a literature study method analyzed using the Miles and Huberman interactive model. The results of the study indicate that novice teachers tend to rely on theory and idealism, while senior teachers are more pragmatic and rely on phronesis in their practice. The professional identity of teachers is formed through the integration of pedagogical, social, personality, and professional competencies, and is influenced by the philosophy of education, social interaction, professional ethics, and adaptation to technology. This article emphasizes the importance of supporting continuous professional development to strengthen the professional identity of teachers in facing the dynamics of today's education.